(untitled) (Global Journal of Science Frontier Research, 2020)
This paper examines the relationship between land ownership, gender inequality and food security in Cameroon with a particular focus on women as food producers, consumers, and family food managers. It examines the constraints women face as farmers in terms of their rights to land ownership, access to production inputs, technology, and food. In most rural areas of Cameroon, women have access to land but are denied ownership rights. Access to land meets the practical gender needs of women but fails to meet the strategic gender needs of land ownership. Besides, women have inadequate access to production inputs and technology in rural Cameroon. In most cases, women still rely on traditional farming methods, limited farm inputs, and rudimentary tools for food production. Most women are also generally excluded from every inheritance and do not benefit from their natal or marital clans and thus have no possibility to control and take decisions over land.